Erbin: an important therapeutic target for blocking tumor metastasis - Qiu, Tingting; Tan, Liquan; Yan, Jialong; Luo, Qunli (Frontiers in Pharmacology, 2024)
Erbin is an adapter protein that interacts with the v-erb-b2 avian erythroblastic leukemia viral oncogene homolog 2 (ERBB2) in epithelial cells. Erbin plays an important role in various signaling pathway including cell proliferation, apoptosis, and autophagy. Additionally, Erbin implicates in the pathogenesis and progression of sepsis and various cancer, including breast cancer, acute myeloid leukemia (AML), hepatocellular carcinoma (HCC) and colorectal cancer (CRC). A recent study shows that loss of Erbin increases the release of acyl-carnitine (Acar) through abolishing interaction with prothrombotic protein ESAM, that promote mitochondrial oxidative phosphorylation in B cells, and ultimately suppresses lung metastasis of CRC. Accordingly, Erbin provides us a new potential treatment of tumor metastasis.